Contributions towards a Dictionary of English Bookcollectors, as also of Some Foreign Collectors, Whose Libraries Were Incorporated in English Collections or Whose Books Are Chiefly Met with in England - Burbidge, Edward (European History and Culture - Book Archive pre-2000., 1969)
An alphabetical Dictionary consisting of 78 extensive articles devoted to illustrious book collectors; the 79th- and last article gives a valuable Roll of book collectors, 1316-1898. The article devoted to every collector is preceded by a biographical sketch, followed by a specification of remarkable works in the collection, and concluded by a short account of the fate of the library, with the devolution of some of its items through successive later collections.